2011
DOI: 10.29333/ejgm/82762
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Radiation on Bone Mineral Density of Radiology Workers Depending on The Device They Use

Abstract: Aim Result: According to the device they use, T-scores of radiology workers (in all groups) were lower than the control group meaningfully (p<0.01). Moreover, T-scores of mri workers was lower than conventional roentgen workers meaningfully (p<0.01). Respectively; MRI Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Regarding published reports ionizing radiation has harmful biological effects on living organisms and this effects increase depending on radiation dose and exposure time to radiation (9,(13)(14)(15)(16). In addition, our study shows that depending on radiation exposure, bone mineral density decreases significantly of all radiology workers compared to control group.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Regarding published reports ionizing radiation has harmful biological effects on living organisms and this effects increase depending on radiation dose and exposure time to radiation (9,(13)(14)(15)(16). In addition, our study shows that depending on radiation exposure, bone mineral density decreases significantly of all radiology workers compared to control group.…”
Section: Discussionsupporting
confidence: 57%
“…The relationship between exposures to low dose ionizing radiation and low bone mineral density is strong. This decrease changes depending on the time and level of radiation exposure of radiology workers (9). Animal experiments have shown that bone mineral density at exposed to radiation is lower and osteoporosis can occur (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…43 Kunt and Dayıoğlu and Kunt et al found in their study conducted on the radiology employee that the lowest densitometry level was in MRI employee. 44 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…In spite of all such clinical uses it is considered to have many deleterious effects in vicinity of living organisms and biological environments, known as mercury toxicity. 9 Mercury is a toxic element which can damage various organs such as central nervous system, renal, respiratory and hematologic systems 10,11 . Some of the horrible threats of the mercury is its concentration in the brain tissues, and its hazardous effects on the nervous system, and its trace has been found in many diseases such as Alzheimer's 12 and Parkinson's disease, and more recently heart failure.…”
Section: Int J Adv Res 8(01) Xx-xxmentioning
confidence: 99%